2015
DOI: 10.1111/jpm.12199
|View full text |Cite
|
Sign up to set email alerts
|

Managing and caring for distressed and disturbed service users: the thoughts and feelings experienced by a sample of English mental health nurses

Abstract: This paper reports the thoughts and feelings experienced by registered mental health nurses caring for distressed and/or disturbed service users in acute inpatient psychiatric settings in England. The prevailing thoughts of nurses were of cognitive dissonance and the conflict between benevolence and malevolence if coercive measures were seen as negative rather than positive; prevailing feelings experienced by nurses were fear, anxiety and vulnerability. To enhance care quality, nurses expressed the need for be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 45 publications
3
59
0
3
Order By: Relevance
“…Nurses have been reported to experience cognitive dissonance, conflicts between benevolence and malevolence, and feelings of fear, anxiety, and vulnerability (Chambers et al . ). Ideals about having dialogues with patients might contradict with the reality of patient care, resulting in an unsatisfactory work situation and feelings of insufficiency (Graneheim et al .…”
Section: Introductionmentioning
confidence: 97%
“…Nurses have been reported to experience cognitive dissonance, conflicts between benevolence and malevolence, and feelings of fear, anxiety, and vulnerability (Chambers et al . ). Ideals about having dialogues with patients might contradict with the reality of patient care, resulting in an unsatisfactory work situation and feelings of insufficiency (Graneheim et al .…”
Section: Introductionmentioning
confidence: 97%
“…Chambers et al . () similarly reported on dual experiences by registered mental health nurses when caring for distressed patients. The nurses experienced cognitive dissonance, such as struggling between compassion and indignity, and feelings of vulnerability and unease.…”
Section: Introductionmentioning
confidence: 99%
“…Literature overwhelmingly reports that professionals believe they use seclusion only as a last resort when faced with violence and aggression (Chambers et al . ). Likewise, the review found that an ongoing threat of violence and aggression was a primary factor in their decision‐making.…”
Section: Discussionmentioning
confidence: 97%
“…When faced with actual or threatened violence, mental health professionals believe they use seclusion to maintain safety rather than for any therapeutic value (Chambers et al . ). Similarly, the review found safety is the main consideration in any decision regarding seclusion.…”
Section: Discussionmentioning
confidence: 97%